Problematics of Multiparty Systems in Indonesia - Aditya Putera Adiguna; Rifaid Rifaid; Zaldi Rusnaedy (Jurnal Pemerintahan dan Politik Lokal, 2020)
Political parties are not only an important part of the many functions they carry out such as representation, recruitment and outreach), but there are complex relationships between parties and form work systems in their political practice. Party system is an analysis to examine party behavior as part of a system, that is, how each party interacts with each other. the party system consists of single parties, dual parties and multiparty parties. This paper tries to identify various kinds of problems caused by the application of a multiparty system by using literature studies based on upstream research. Indonesia is a democratic country that adopts a multiparty system in its political activities which is characterized by the many parties competing for government power. A multiparty system when combined with a presidential government system raises various problems, such as the possibility of electing a minority president, too many parties joining the coalition to become a fat coalition, and the stability of the government is disrupted. Partai politik tidak hanya merupakan bagian penting dari banyak fungsi yang dilakukan seperti perwakilan, rekrutmen dan penjangkauan, tetapi ada hubungan yang kompleks antara partai-partai dan pembentukan sistem kerja dalam praktik politik. Sistem kepartaian adalah analisis untuk memeriksa perilaku partai sebagai bagian dari suatu sistem, yaitu bagaimana masing-masing pihak berinteraksi satu sama lain. sistem kepartaian terdiri dari partai tunggal, dwi-partai dan partai multipartai. Artikel ini mencoba mengidentifikasi berbagai jenis masalah yang disebabkan oleh penerapan sistem multipartai dengan menggunakan studi literatur berdasarkan penelitian terdahulu. Indonesia adalah negara demokratis yang mengadopsi sistem multipartai dalam kegiatan politiknya yang ditandai oleh banyak pihak yang bersaing untuk mendapatkan kekuasaan pemerintah. Sistem multipartai ketika digabungkan dengan sistem pemerintahan presidensial menimbulkan berbagai masalah, seperti kemungkinan memilih presiden minoritas, terlalu banyak partai yang bergabung dalam koalisi untuk menjadi koalisi yang gemuk, dan stabilitas pemerintahan terganggu.